Long-term safety and effectiveness of tocilizumab in patients with rheumatoid arthritis and inadequate responses to csDMARDs and/or TNF inhibitors: an open-label study close to clinical practice - Bykerk, Vivian P; Östör, Andrew J K; Alvaro-Gracia, José; Pavelka, Karel; Román Ivorra, José Andrés; Nurmohamed, Michael T; Luder, Yves; Sidiropoulos, Paris N M; Devenport, Jenny; Sibilia, Jean (Clinical rheumatology, 2019)
OBJECTIVE: To assess the long-term safety, tolerability, and effectiveness of tocilizumab (TCZ) as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in clinical practice in patients with moderate to severe rheumatoid arthritis (RA). METHODS: Patients in the 24-week, open-label ACT-SURE study who had at least a moderate EULAR response by week 24 and were from a participating country were eligible for this long-term extension (LTE); the patients continued to receive TCZ 8 mg/kg intravenously every 4 weeks as monotherapy or in combination with ≥ 1 csDMARD for up to an additional 108 weeks. The primary endpoint was the incidence of adverse events (AEs) and serious AEs (SAEs). Effectiveness endpoints included Disease Activity Score in 28 joints (DAS28) responses, American College of Rheumatology (ACR) responses, and patient-reported outcomes (PROs). RESULTS: Of the 1102 patients who completed the core 24-week study, 934 participated in the LTE; the median exposure to TCZ was 64.3 weeks. From baseline to the end of the LTE, AEs and SAEs occurred in 90% and 9% of patients, respectively. The overall event rates (95% CI) of AEs and SAEs were 406.5 per 100 patient-years (PY) (395.5, 417.8) and 8.8 per 100 PY (7.3, 10.6), respectively. Mean (SD) improvement in DAS28 was 4.12 (1.18), P < 0.0001. The DAS28 remission rates, ACR response rates, and PRO scores were maintained during the LTE study. CONCLUSION: In clinical practice, TCZ as monotherapy or in combination with csDMARDs was safe, well tolerated, and efficacious in patients with moderate to severe RA.
Keywords: výsledek terapie; Young Adult; Male; mladý dospělý; kombinovaná farmakoterapie; Adult; Aged; dospělí; mužské pohlaví; senioři; Drug Therapy, Combination; Severity of Illness Index; Glucocorticoids; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; senioři nad 80 let; revmatoidní artritida; Arthritis, Rheumatoid; lidé; glukokortikoidy; ženské pohlaví; Humans; inhibitory TNF; Antirheumatic Agents; antirevmatika; Aged, 80 and over; Tocilizumab; Tumor Necrosis Factor Inhibitors; Safety; stupeň závažnosti nemoci; Rheumatoid arthritis; Female; Monotherapy; lidé středního věku; Middle Aged